Histogenesis and Urban Growth in Supaul Town, Bihar - Kumar, Ramawadhesh; Meena, M. L. (National Geographical Journal of India, 2022)
Histogenesis and urban growth of any town passes through several phases of development, phase adds something for its different dimensions. It depends upon the humanenvironment relationship in plain of resource base and its interaction, that how much any phase of growth is either boon or bane for that area. In the present study an attempt is made to analyse the history of Supaul town in Kosi plain wherein Mithila culture survived in upheaval situation of turbulent river. Supaul town luckily came under Supaul subdivision as early as in 1870s than the other towns of this region. But the natural factors especially swinging course of Kosi River abruptly broke all the linkages and communication for a significant period up to independence and the administrative edge could not be plugged in for its betterment. The objective of this paper is to find out the significant milestones and changes through its histogenesis and evolution. Supaul town has a long historicity, though geographically it often faces constraints either in connectivity or development. A new hope is likely to usher in town after integration of modern infrastructures and peoples participation. Both primary and secondary data have been analysed here with the help of Arc GIS 9.3 to analyse the pattern of histogenesis. Existing status of urban growth is measured through extensive field investigation survey, as well as field observation and cartographic techniques which are used for the interpretation of the study